Comparable analysis of shielding layer parameters for different target materials under the plasma stream exposure - Tsarenko, A.V.; Trubchaninov, S.A.; Marchenko, A.K.; Chebotarev, V.V.; Staltsov, V.V.; Tereshin, V.I.; Garkusha, I.E.; Makhlaj, V.A.; Solyakov, D.G.; Landman, I.S. (Вопросы атомной науки и техники, 2005)
Numerous experiments on the plasma-wall interaction problem have been performed with the powerful quasistationary plasma accelerator (QSPA) K-50 device during last decades. These investigations were performed with different target materials (carbon, tungsten, steel etc.) at the different plasma stream parameters. But such problems as, for example, impact of target material on the basic plasma characteristics at the same plasma stream parameters were unsolved. So this paper is summarizing data of researches of plasma shielding layer using different materials of targets. The plasma parameters (peak values) obtained at the longitudinal magnetic field B=0.54 T were as follows: Ne~10¹⁷ cm⁻³ (measured from Hβ linear Stark-effect), Te~2.7 eV, plasma pressure ~16 Bar. Working gas was hydrogen with a small diagnostics dope of nitrogen. Останнім часом були представлені численні експерименти з проблеми взаємодії плазма-стінка, які проводилися на квазістаціонарному плазмовому прискорювачі (КСПП) Х-50. Ці дослідження були представлені з різними матеріалами мішеней (вуглець, вольфрам, сталі та ін.) при різних параметрах плазмового потоку. Такі проблеми, як вплив матеріалу мішені на основні характеристики плазми при однакових параметрах плазмового потоку досі не вирішені. Тому ця стаття підводить підсумки досліджень перехідного шару плазми з використанням різних матеріалів мішеней. Параметри плазми (максимальні величини) у магнітному полі B=0.54 T такі: Ne~10¹⁷ см⁻³ (виміряні по лінійному Штарк-ефекту Hβ), Te~2.7 eВ, плазмовий тиск ~16 Бар. В ролі робочого газу використовувався водень з невеликим додатком азоту. В последнее время были представлены многочисленные эксперименты по проблеме взаимодействия плазма-стенка, которые проводились на квазистационарном плазменном ускорителе КСПУ Х-50. Эти исследования представлялись с использованием различных материалов мишеней (углерод, вольфрам, сталь и др.) при разных параметрах плазменного потока. Такие проблемы, как влияние материала мишени на основные характеристики плазмы при одинаковых параметрах потока, все еще не решены. Поэтому эта работа подводит итоги исследований переходного плазменного слоя с использованием различных материалов мишеней. Параметры плазмы (пиковые значения) в продольном магнитном поле B=0.54 T следующие: Ne~10¹⁷ см⁻³ (определялось по линейному Штарк-эффекту Hβ ), Te~2.7 эВ, давление плазмы ~16 Бар. В качестве рабочего газа использовался водород с небольшой добавкой азота.